MATERNAL OCCUPATION AND THE NUTRITIONAL STATUS OF CHILDREN AGED 6-24 MONTHS IN THE TAMALE METROPOLIS - Abubakari, A.; Inusah, A-K.; Latifa, A. A.; Hakeem, R.; Wumbei, A.; Yahaya, I. A.; Yahaya, I. A. (UDS International Journal of Development, 2023)
Adequate nutrition is essential in early childhood to ensure proper organ formation and function, a strong immune system and cognitive development. The present study sought to assess the influence of maternal occupation on the nutritional status of children aged 6-24 months in the Tamale metropolis. An analytical cross-sectional survey was carried out on 240 women and their children aged 6-24 months who sought child welfare clinic (CWC) services at Tamale West and Tamale Central Hospitals and Nyohini clinic in the Tamale metropolis. A semi-structured questionnaire was used to collect information on mother’s socio economic and demographic features, feeding practices and child characteristics. The SECA weighing scale and measuring board was used to measure weight and height respectively. The data was analyzed using the Statistical Package for Social Science (SPSS) version 21. The prevalence of wasting, stunting and underweight were 28.3%, 9.6% and 18.3% respectively. The prevalence of stunting was high among children whose mothers work in the formal sector (18.5%) followed by children of mothers who were housewives (10.8%) and low among those whose mothers work in the informal sector (7.6%). Wasting prevalence was high among unemployed/housewives (37.5%), followed by informal workers (27.4%) and formal workers (14.8%). Stunting was statistically significantly associated with mother’s occupational and monthly income. Stunting was about seven (7) times higher among children of mothers who are employed in the formal sector than those of mothers employed in the informal sector. Mother’s monthly income was negatively associated with wasting, as mothers who earned less than 500 Ghana cedis were more likely to have stunted children compared to those who earned 500 Ghana cedis or more. Time spent at work by mother was also statistically significantly associated with child wasting and underweight. Formal sector employment and monthly income were identified as determinant of stunting. Also, time spent at work by mothers could influence the nutritional status of their children. Keywords: Maternal Occupation, Nutritional Status, Children